2022
DOI: 10.3390/jimaging8050123
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Imaging for Early Breast Cancer Detection: Current State, Challenges, and Future Directions

Abstract: Breast cancer is the most commonly diagnosed cancer type and is the leading cause of cancer-related death among females worldwide. Breast screening and early detection are currently the most successful approaches for the management and treatment of this disease. Several imaging modalities are currently utilized for detecting breast cancer, of which microwave imaging (MWI) is gaining quite a lot of attention as a promising diagnostic tool for early breast cancer detection. MWI is a noninvasive, relatively inexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 125 publications
(151 reference statements)
0
30
0
Order By: Relevance
“…To have the best possible results, some works propose that the tissue must be immersed in a liquid [ 25 ]. In this sense, some works have proposed acquisition systems that deal with this issue [ 26 , 27 , 28 , 29 ].…”
Section: Technologies Used To Obtain Breast Tissue Imagesmentioning
confidence: 99%
“…To have the best possible results, some works propose that the tissue must be immersed in a liquid [ 25 ]. In this sense, some works have proposed acquisition systems that deal with this issue [ 26 , 27 , 28 , 29 ].…”
Section: Technologies Used To Obtain Breast Tissue Imagesmentioning
confidence: 99%
“…In addition to the common advantages mentioned above, MWI methods show other benefits such as appropriate spatial resolution and image depth for breast tumour detection, the possibility of early detection and tumour detection in dense breasts (especially needed for young patients), relatively low cost and reduced measurement-processing and image-generation times. In this sense, medical imaging systems based on signals with microwave-range frequencies are rising as a promising technique for on-time detection of this kind of breast cancer [ 4 , 8 ]. Moreover, microwave-based images can be used for the detection and characterisation of biological materials [ 9 ], thus providing interesting additional information.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas tomography techniques can achieve remarkable precision, the image-generation processing usually requires considerable time, even dozens of minutes [ 19 , 20 ]. Radar techniques, conversely, can produce the images in a faster manner with similar precision [ 8 ], although they require sophisticated calibration techniques [ 4 ], usually made with in-lab measurements of biological phantoms.…”
Section: Introductionmentioning
confidence: 99%
“…Ongoing research in the inverse scattering and microwave imaging communities has shown that the reconstruction of models of the human breast can provide information on the structure and material properties of breast tissue both synthetically and experimentally [1,2]. Microwave imaging technologies do not generate high resolution images like those obtained from x-ray or computed tomography (CT), but by using microwaves rather than x-rays, the technology is beneficial as it relies on non-ionizing radiation and may have utility as a lower-cost screening tool [3]. An effective screening tool would provide information to characterize different tissue regions within the breast based on location, geometry, and physical properties of the tissue.…”
Section: Introductionmentioning
confidence: 99%